2021
DOI: 10.35868/1997-3004.33.25-32
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nodule Bacteria Strains of Sinorhizobium Meliloti on the Amino Acid Content in the Tops of Alfalfa Under Different Water Supply

Abstract: Objective. To study the amino acid composition in the tops of alfalfa under different water supply (60 % MVC (maximum water capacity) and 30 % MVC) depending on the inoculum strain (Sinorhizobium meliloti 425a, T17, AC08). Methods. Microbiological (bacterial cultivation), physiological (vegetation experiment), biochemical (determination of amino acid content in the tops of plants). Results. It was established that the qualitative amino acid composition in the tops of ALFALFA was identical in all variants. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In field trials, bean yields on low fertility soils increased by an impressive 126 % (Razafintsalama et al, 2022). It was shown that pre-sowing inoculation of alfalfa plants with the active strains of Sinorhizobium meliloti led to an increased production of amino acids, in particular essential amino acids in above ground mass under optimal moisture and insufficient water supply (Kots et al, 2021), showing the role of nitrogen fixers in plant biofortification.…”
Section: Introductionmentioning
confidence: 99%
“…In field trials, bean yields on low fertility soils increased by an impressive 126 % (Razafintsalama et al, 2022). It was shown that pre-sowing inoculation of alfalfa plants with the active strains of Sinorhizobium meliloti led to an increased production of amino acids, in particular essential amino acids in above ground mass under optimal moisture and insufficient water supply (Kots et al, 2021), showing the role of nitrogen fixers in plant biofortification.…”
Section: Introductionmentioning
confidence: 99%